2019
DOI: 10.1002/jbm.b.34325
|View full text |Cite
|
Sign up to set email alerts
|

Topical film prepared with Rhus verniciflua extract‐loaded pullulan hydrogel for atopic dermatitis treatment

Abstract: Atopic dermatitis (AD) is characterized by relapsing pruritus and skin dryness. Due to the pathogenic multiplicity and the adverse effects associated with the current therapeutics, development of transdermal drug delivery system is becoming an area of interest. Here, a novel topical film prepared with Rhus verniciflua extract (RVE)‐loaded pullulan hydrogel (RVE@PH) was synthesized and tested its therapeutic efficacy on the AD rats modeled by neonatal capsaicin injection method. The RVE@PH was characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…It is noteworthy that the addition of AbE to the polymer matrix improved its wound healing activity. Recently, several studies have already incorporated natural products into polymeric systems for wound dressings applications, including membranes, hydrogels and scaffolds 44–46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the addition of AbE to the polymer matrix improved its wound healing activity. Recently, several studies have already incorporated natural products into polymeric systems for wound dressings applications, including membranes, hydrogels and scaffolds 44–46 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have already incorporated natural products into polymeric systems for wound dressings applications, including membranes, hydrogels and scaffolds. [44][45][46] Extracts rich in sugars or polysaccharides can act by stimulating the angiogenesis process, which accelerates the wound healing. [47][48][49] Furthermore, topical treatment of wounds with sugars promotes the nutrition of the skin and reduces inflammation, as well stimulates the process of re-epithelialization of the injured tissue.…”
Section: Evaluation Of Wound Healing Properties Of the Formulationsmentioning
confidence: 99%
“…The film demonstrated significant attenuation in dermatitis score, epidermal thickness, mast cell infiltration, and serum myeloperoxidase activities compared to plain gel and non-treated rat groups. The results revealed that the film inhibits atopic dermatitis through exerting dual roles: Rhus verniciflua extract mediated pharmaceutical and pullulan-mediated physical actions (Jeong et al, 2019). Vishwanath et al (2012) developed a transdermal film of metoprolol succinate with the blend of pullulan and poly(acrylamide).…”
Section: Pullulanmentioning
confidence: 99%
“…Overall uniformity, drug content, anti-arthritis efficacy, film thickness, tensile strength, percentage elongation, folding durability, moisture absorption, moisture loss, and moisture gain were all evaluated 7 .…”
Section: Evaluation Of Chitosan Loaded Transdermal Filmsmentioning
confidence: 99%